Predictors of poor prognosis in healthy, young, individuals with SARS-CoV-2 infections - Espejo-Paeres, Carolina; Espliguero, Ramón Arroyo; Uribarri, Aitor; Antón-Huguet, Berta; Romero, Rodolfo; Fernández-Rozas, Inmaculada; Becerra-Muñoz, Víctor Manuel; Alfonso-Rodríguez, Emilio; Huang, Jia; Ortega-Armas, María Elizabeth; Pepe, Martino; González, Adelina; et al. (Clinical microbiology and infection, 2022)
Objectives - To identify predictors of poor prognosis in previously healthy young individuals admitted to hospital with coronavirus disease 2019 (COVID-19). - Methods - We studied a cohort of patients hospitalized with COVID-19. All patients without co-morbidities, without usual treatments and ≤65 years old were selected from an international registry (HOPE-COVID-19, NCT04334291). We focused on baseline variables—symptoms and signs at admission—to analyse risk factors for poor prognosis. The primary end point was a composite of major adverse clinical events during hospitalization including mortality, mechanical ventilation, high-flow nasal oxygen therapy, prone, sepsis, systemic inflammatory response syndrome and embolic events. - Results - Overall, 773 healthy young patients were included. The primary composite end point was observed in 29% (225/773) and the overall mortality rate was 3.6% (28/773). In the combined event group, 75% (168/225) of patients were men and the mean age was 49 (±11) years, whereas in the non-combined event group, the prevalence of male gender was 43% (238/548) and the mean age was 42 (±13) years (p < 0.001 for both). On admission, respiratory insufficiency and cough were described in 51.4% (114/222) and 76% (170/223) of patients, respectively, in the combined event group, versus 7.9% (42/533) and 56% (302/543) of patients in the other group (p < 0.001 for both). The strongest independent predictor for the combined end point was desaturation (Spo2 <92%) (OR 5.40; 95% CI 3.34-8.75; p < 0.001), followed by tachypnoea (OR 3.17; 95% CI 1.93-5.21; p < 0.001), male gender (OR 3.01; 95% CI 1.96-4.61; p < 0.001) and pulmonary infiltrates on chest X-ray at admission (OR 2.21; 95% CI 1.18-4.16; p 0.014). - Conclusions - Major adverse clinical events were unexpectedly high considering the baseline characteristics of the cohort. Signs of respiratory compromise at admission and male gender, were predictive for poor prognosis among young healthy patients hospitalized with COVID-19.
Available online 30 September 2021
Gesehen am 10.08.2023